The awareness of culture and tradition of Malay Sarawak community / Siti Aisyah Abdul Latif - Abdul Latif, Siti Aisyah (2015)
Tradition is the passing of beliefs from one generation to the next. Culture consists of the features that describe a society at any given time. Tradition often remains the same over time. Culture changes continuously, even within the same society. This research study has been conducted to investigate various factor that predict the awareness of culture and tradition of Malay Sarawak community. A conceptual framework comprises of four (4) factors which is concrete expression, recognize behaviours, explicit belefs and deeply embedded beliefs are used to examine the awareness of culture and tradition of Malay Sarawak community.